A semiotic analysis of the tolerance boundaries in Fī Ẓilāl al-Qur’ān in Fuṣṣilat verse 34 - Windariyah, Devi Suci (Universitas Mulawarman, 2025)
This research analyzes the limits of tolerance in Sayyid Qutb's Fī Ẓilāl al-Qur’ān using Roland Barthes' semiotic approach. The phenomenon of religious tolerance in this tafsir reflects the need for clear boundaries for Muslims in dealing with differences, especially in the midst of conflict over the meaning of tolerance between Western and Islamic perspectives. Roland Barthes' semiotic method is used to identify and interpret the three levels of meaning in the tafsir, namely denotation, connotation, and myth. The main findings show that the limits of tolerance in Islam include the ability to distinguish between good and evil, limiting tolerance to personal issues without involving aqidah, and rejecting evil with good patiently and wisely. The study concludes that the connotative and mythical meanings in this text serve as profound social advice, which not only maintains religious values but also supports social harmony. The contribution of this research is to enrich semiotic studies in Islamic studies, especially in the context of tolerance. This research is relevant for understanding the limits of tolerance that can be applied in a global and multicultural context, as well as strengthening the relationship between semiotic theory and Qur'anic interpretation.